Sosialisasi Undang-Undang Perlindungan Data Pribadi (UU PDP) guna Meningkatkan Kesadaran Keamanan Data Pribadi Masyarakat di Kelurahan Serua, Bojongsari, Depok - Situmeang, Nurmasari; Salam, Syahrul; Setiadarma, Aan; Talmullah, Ali Zhafir; Utami, Rahmadini Agung Ayu (Turast: Jurnal Penelitian dan Pengabdian, 2024)
Digital transformation is one of the priority programs during Joko Widodo's administration. Digital transformation brings the government bureaucratic governance system into the e-government era. This digital transformation in the bureaucratic sector makes public services easier and is a means of data transparency. The digitalization of bureaucracy also facilitates government performance in certain fields, especially administration. However, bureaucratic digitalization efforts are faced with challenges in the form of data breach crimes. As a result, there are still doubts in society regarding the bureaucratic digitalization system. Socialization regarding understanding the PDP Law is an effort contributed by educational staff which aims to spread awareness about the law itself and the importance of maintaining the security of personal data. The aim is to increase people's caution in handing over their personal data in the digital realm. This socialization was carried out in Serua Village, Depok City involving members of the Healthy Village Working Group. The results of the outreach activities showed an increase in participants' understanding and awareness of the benefits of the PDP Law and the importance of protecting personal data. After receiving socialization, the participants became knowledgeable about what features are useful for protecting their data on their respective devices. Apart from that, participants also viewed that the PDP Law could protect their personal data because the law reflected law enforcement efforts for people's personal data.Transformasi digital adalah salah satu program prioritas di masa pemerintahan Joko Widodo. Transformasi digital membawa sistem tata kelola birokrasi pemerintahan ke era e-government. Transformasi digital di sektor birokrasi ini mempermudah pelayanan publik serta sebagai sarana transparansi data. Digitalisasi birokrasi juga memudahkan kinerja pemerintah di bidang tertentu, khususnya administrasi. Namun, upaya digitalisasi birokrasi dihadapkan pada tantangan berupa kejahatan pembobolan data. Dampaknya, masih terdapat keraguan dalam masyarakat terhadap sistem digitalisasi  birokrasi. Sosialisasi mengenai pemahaman UU PDP merupakan upaya kontribusi dari tenaga pendidik yang bertujuan untuk menyebarkan kesadaran mengenai undang-undang itu sendiri serta pentingnya menjaga keamanan data pribadi. Tujuannya adalah untuk meningkatkan kehati-hatian masyarakat dalam menyerahkan data pribadi mereka di ranah digital. Sosialisasi ini dilakukan di Kelurahan Serua, Kota Depok dengan melibatkan anggota Pokja Kelurahan Sehat. Hasil kegiatan sosialisasi menunjukkan adanya peningkatan pemahaman dan kesadaran peserta terhadap manfaat UU PDP serta pentingnya melindungi data pribadi. Setelah mendapatkan sosialisasi, para peserta menjadi memiliki pengetahuan terkait fitur apa saja yang bermanfaat bagi perlindungan data mereka di gawai masing-masing. Selain itu, peserta juga memandang bahwa UU PDP dapat melindungi data pribadi mereka adalah karena undang-undang tersebut mencerminkan upaya penegakan hukum bagi data pribadi masyarakat.